Potentials of genotypes, morpho-physio-biochemical traits, and growing media on shelf life and future prospects of gene editing in tomatoes - Yadav, Renu; Jaiswal, Sarika; Singhal, Tripti; Mahto, Rohit Kumar; Verma, S. B.; Yadav, Ramesh Kumar; Kumar, Rajendra (Frontiers in Genome Editing, 2023)
Background: Field experimentations were led in randomized block designs during rabi seasons of the years 2018-2019 and 2019-2020 to study genetic basis for impact of genotypes and morpho-physio-biochemical traits under varied organic and inorganic fertiliser dozes on shelf-life attribute of tomatoes. The experiment comprised of three diverse nutritional ambient (T1-Organic; T2 -Inorganic, T3 -Control (without any fertilizers)) and five tomato genotypes of variable growth habits specifically Angoorlata (Indeterminate), Avinash-3 (semi determinate), Swaraksha (semi-determinate), Pusa Sheetal (semi-determinate) and Pusa Rohini (determinate).The diverse tomato genotypes behaved apparently different from each other for shelf life. All genotypes gave maximum shelf life grown in organic ambient. However, Pusa Sheetal gave maximum shelf life of 8.35 days when grown in organic ambience and showed an increase of 12% over the control. The genotype Pusa Sheetal, organic ambience and biochemical trait Anthocyanin have proved to be potential contributors towards enhanced shelf life in tomato.The genotype Pusa Sheetal a novel source for shelf life, organic ambience andAnthocyanin have proved to be potential contributors towards enhanced shelf life in tomato.Thus, identified trait and genotype may be utilized in tomato improvement programs. Further, this identified trait can also be targeted for their quantity enhancement in order to increase the tomato shelf life through genome editing approach. Accordingly, a generalized genome editing mechanism is proposed.